Extracellular membrane vesicles harbouring viral genomes. (27th August 2013) - Gaudin, Marie; Krupovic, Mart; Marguet, Evelyne; Gauliard, Emilie; Cvirkaite‐Krupovic, Virginija; Le Cam, Eric; Oberto, Jacques; Forterre, Patrick
Summary Cells from the three domains of life produce extracellular membrane vesicles (MVs), suggesting that MV production is a fundamental aspect of cellular physiology. We have recently shown that MVs produced by the hyperthermophilic archaeon Thermococcus kodakaraensis can be used as vehicles to transfer exogenous recombinant plasmid DNA from cell to cell. Here, we show that Thermococcus nautilus, which harbours three plasmids, pTN1, pTN2 and pTN3, produces MVs, and that some of them selectively incorporate pTN1 and pTN3. Interestingly, pTN3 represents the genome of a defective virus, which encodes signature proteins common to a large group of viruses infecting hosts from all three cellular domains. However, preparations of MVs produced by T. nautilus have a protein composition similar to that of classical MVs from Thermococcales and do not contain the viral major capsid protein encoded by pTN3. Our results suggest that MVs can serve as vehicles for the intercellular transport of viral genomes and facilitate recombination between viral, plasmid and/or cellular chromosomes in the absence of viral infection.